Penerapan Model Problem Based Learning Berbasis Berdiferensiasi berdasarkan Gaya Belajar Peserta didik pada Pelajaran Biologi Materi Ekosistem Kelas X SMA - Irfiani Shafira; Fifi Fatmawati Rahayu; Fatihatunnisa Ridha Rahman; Julia Mawarni; Dian Fitriani (Journal on Education, 2023)
This study aims to apply the Differentiated Problem Based Learning (PBL) model in Biology learning Ecosystem material by considering students' learning styles. PBL is a learner-centered learning approach and involves students to be active in the process of solving problems through investigation and collaboration between students. This research was conducted using a qualitative descriptive research method in class X at a high school in Serang City. Data on students' learning styles were collected using observation techniques through questionnaires. The results showed that there was a diversity of student learning styles, with most students identifying visual learning styles. In addition, the application of differentiation-based PBL has a positive impact because it can express potential according to their interests so as to provide a more meaningful learning experience for them.